Carbon Absorbing Vegetation and Enhancement of Ecosystem Benefits on Residential Environment - Putranty Widha Nugraheni; Jumiati Jumiati; Yulisa Fitrianingsih (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2022)
With the increase in population, mainly in urban sprawls, the available vegetation decreases due to land conversion into the residential area. At the same time, the rise in population is proportional to the increase in air pollution, which is characterized by the Greenhouse Gases (GHG) problems. However, naturally, vegetation can absorb greenhouse gas emissions as a component in the photosynthesis process. Increasing space for housing is balanced with spatial regulations for the use of built-up land so that some of the carbon emissions from daily activities are reduced. Based on the research, there is still a difference between carbon absorption and carbon emissions; therefore, increasing the amount of vegetation as a Green Open Space (GOS) needs to be maximized based on the number and type of plants. The air pollution problem is attempted to be done naturally so that the ecosystem will naturally reduce the existing pollutants. The Community Service (CS) stages starting from land preparation, seed preparation, pathway construction, monitoring plantation, can be a solution to answer the problems of city dwellers on a housing scale. The overall implementation of the community services has gone well, such as constructing access pathways, planting trees and flower plants, and using land for public housing facilities into parks. The environment will be safer from wild and dangerous animals to create a better environment.